Constellating Chartist Poetry: Gerald Massey, Walter Benjamin, and the Uses Of Messianism. - Sanders, Michael (Victorian Poetry)
The article looks at poets Gerald Massey and Walter Benjamin and compares their style of chartist poetry and the uses of Messianism. The article states that both poets focus on the idea that the past and present are temporal. Also discussed is their idea that a poet's purpose is to create a temporal alignment of the past and present, thus creating a constellation where pieces of Messianic time can be gathered together and used to create a different social order for the future.